Orally Bioavailable Proteolysis-Targeting Chimeras: An Innovative Approach in the Golden Era of Discovering Small-Molecule Cancer Drugs - Rohan Kalyan Rej; Srinivasa Rao Allu; Joyeeta Roy; Ranjan Kumar Acharyya; I. N. Chaithanya Kiran; Yesu Addepalli; V. Dhamodharan (MDPI AG, 2024)
Proteolysis-targeting chimeras (PROTACs) are an emerging therapeutic modality that show promise to open a target space not accessible to conventional small molecules via a degradation-based mechanism. PROTAC degraders, due to their bifunctional nature, which is categorized as 'beyond the Rule of Five', have gained attention as a distinctive therapeutic approach for oral administration in clinical settings. However, the development of PROTACs with adequate oral bioavailability remains a significant hurdle, largely due to their large size and less than ideal physical and chemical properties. This review encapsulates the latest advancements in orally delivered PROTACs that have entered clinical evaluation as well as developments highlighted in recent scholarly articles. The insights and methodologies elaborated upon in this review could be instrumental in supporting the discovery and refinement of novel PROTAC degraders aimed at the treatment of various human cancers.